Systemic risk and macro-prudential policies: A credit network-based approach - Ermanno Catullo; Mauro Gallegati; Antonio Palestrini (Kiel University, FinMaP - Financial Distortions and Macroeconomic Performance, 2015)
Assessing systemic risk and defining macro-prudential policies aiming at reducing economic system vulnerability have been at the center of the economic debate of the last years. Credit networks play a crucial role in diffusing and amplifying local shocks, following the network-based financial accelerator approach (Delli Gatti et al., 2010; Battiston et al., 2012), we constructed an agent based model reproducing an artificial credit network populated by heterogeneous firms and banks. Calibrating the model on a sample of firms and banks quoted on Japanese stock-exchange mar- kets from 1980 to 2012, we try to define both early warning indicators of crises and policy precautionary measures based on the analysis of the endogenous dynamics of credit network connectivity.
info:eu-repo/grantAgreement/EC/FP7/612955
Keywords: 330